Dispute Over Vote Count in the Election of The Head of Huta Julu Village, Mandailing Natal Regency From the Perspective of Fiqh Siyasah (Analysis Study of Decision Number: 73/G/2023/PTUN.MDN) - Nisyatu Zahra Azharani; Ramadani (Dinasti Research, 2024)
Law Number 6 of 2014 outlines the authority, responsibilities, and processes related to the election and dismissal of village heads. This study examines the mechanisms applied by Indonesian law to resolve disputes related to village head elections. The relevant decision is 73/G/2023/PTUN.MDN. This study uses normative legal research, which involves the analysis of laws and regulations as legal documents. Research findings indicate a discussion regarding the selection of village heads in Huta Julu, a community in Mandailing Natal Regency. Village leaders are appointed directly, bypassing the resolution of existing issues, while disputes regarding fair vote distribution by the election committee are handled unfairly. This study explains the strategies used by judges in resolving disputes that occurred during the village head election in Huta Julu.